1990
DOI: 10.1007/bf00117788
|View full text |Cite
|
Sign up to set email alerts
|

N-methylformamide affects spontaneous metastases of 3LL lines and increases natural killer activity of tumor-bearing mice

Abstract: The antitumor activity of the polar solvent N-methylformamide (NMF) was evaluated on three lines derived from the Lewis lung carcinoma (3LL), endowed with different metastatic potential. Two administration schedules were tested, these being repeated regimens of NMF (200 mg/kg per dose) for 12 consecutive days, starting 24 h or 6-10 days after tumor implantation (early or late treatment, respectively). The results of the present work can be summarized as follows: (1) NMF regimens did not greatly affect tumor gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The effect of NMF on spontaneous metastases has also been demonstrated previously in different model systems, and several mechanisms have been postulated for the antimetastatic effect of the agent (Iwakawa et al, 1987;Tofilon et al, 1987;Iwakawa et al, 1989;Greco et al, 1990;Iwakawa et al, 1994). It has been hypothesized that NMF may induce tumour cells to form a less aggressive differentiated phenotype, resulting in a decrease in metastatic potential (Spremulli and Dexter, 1984).…”
Section: Effect Of Anti-integrin Antibodies On Cell Adhesionmentioning
confidence: 73%
See 4 more Smart Citations
“…The effect of NMF on spontaneous metastases has also been demonstrated previously in different model systems, and several mechanisms have been postulated for the antimetastatic effect of the agent (Iwakawa et al, 1987;Tofilon et al, 1987;Iwakawa et al, 1989;Greco et al, 1990;Iwakawa et al, 1994). It has been hypothesized that NMF may induce tumour cells to form a less aggressive differentiated phenotype, resulting in a decrease in metastatic potential (Spremulli and Dexter, 1984).…”
Section: Effect Of Anti-integrin Antibodies On Cell Adhesionmentioning
confidence: 73%
“…It has been hypothesized that NMF may induce tumour cells to form a less aggressive differentiated phenotype, resulting in a decrease in metastatic potential (Spremulli and Dexter, 1984). In a previous paper we demonstrated that NMF produces a significant increase in splenic NK cell activity in Lewis lung carcinoma-bearing mice and we suggested that NMF could promote differentiation of NK precursor cells in tumour-bearing hosts in which maturation defects had been caused by the neoplastic disease (Greco et al, 1990). Alternatively, NMF could act as an immunomodulating agent whose effect is specifically detectable in immunodepressed hosts (Parhar and Lala, 1985).…”
Section: Effect Of Anti-integrin Antibodies On Cell Adhesionmentioning
confidence: 79%
See 3 more Smart Citations